(untitled) (Economic studies journal, 2023)
The research aimed to identify the degree of application of knowledge management in the faculties of the University of Misrata from the point of view of the faculty members, whose number is (1250) in all the university’s faculties. To achieve the research objectives, the descriptive approach was used and a questionnaire consisting of (20) items divided into four areas was prepared and distributed to A random sample of faculty members in the targeted colleges was taken from (132) questionnaire papers, and statistical processing was conducted using the statistical analysis program (SPSS). The most important results of the research were as follows: The degree of application of knowledge management in the faculties of Misurata University was average, and there were no statistically significant differences between the opinions of the research sample in the degree of application of knowledge management in the faculties of Misurata University according to the variables (degree - years of experience), while the results showed that there were statistically significant differences between the opinions of the sample The research is according to the college variable and for the benefit of faculty members in the College of Education.